PENGARUH MODEL GAME BASED LEARNING BERBANTUAN MEDIA VIDEO ANIMASI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV - Kadek Sukra Suantari; I Made Ari Winangun; Putu Eka Sastrika Ayu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Science and Social Studies (IPAS) learning in elementary schools continues to face challenges in fostering student engagement, resulting in suboptimal learning outcomes. This condition highlights the need for instructional strategies that integrate interactive learning activities with instructional materials presented in ways that facilitate conceptual understanding. This study examined the effect of implementing the Game Based Learning model assisted by animated video media on the Science and Social Studies (IPAS) learning outcomes of fourth-grade students in Cluster V Elementary Schools, Kubutambahan District. A quasi-experimental approach employing a pretest–posttest control group design was conducted with 58 students selected through Simple Random Sampling. Data were analyzed using an independent sample t-test supported by N-Gain analysis. The findings revealed that students who learned through the Game Based Learning model assisted by animated video media achieved greater improvement in learning outcomes (N-Gain = 61.06; moderate category) than those who received conventional instruction (N-Gain = 30.36; low category), with the difference being statistically significant. These findings extend the empirical evidence that the effectiveness of Science and Social Studies (IPAS) learning is influenced not merely by the use of instructional models or digital media independently, but by the integration of both in creating meaningful learning experiences that support students' conceptual understanding. The results also provide a foundation for developing more adaptive and contextually relevant Science and Social Studies (IPAS) instruction in elementary schools. ABSTRAK Pembelajaran IPAS di sekolah dasar masih menghadapi tantangan dalam menciptakan keterlibatan peserta didik yang berdampak pada belum optimalnya hasil belajar. Kondisi tersebut mengindikasikan perlunya strategi pembelajaran yang mampu mengintegrasikan aktivitas belajar yang interaktif dengan penyajian materi yang lebih mudah dipahami. Kajian ini dilakukan untuk menguji pengaruh penerapan model Game Based Learning berbantuan media video animasi terhadap hasil belajar IPAS siswa kelas IV SD Gugus V Kecamatan Kubutambahan. Penelitian menerapkan pendekatan quasi experiment dengan rancangan pretest–posttest control group design pada 58 siswa yang dipilih melalui teknik Simple Random Sampling. Analisis dilakukan menggunakan independent sample t-test yang didukung analisis N-Gain. Hasil penelitian menunjukkan bahwa kelas yang mengikuti pembelajaran melalui Game Based Learning berbantuan media video animasi memperoleh peningkatan hasil belajar yang lebih tinggi (N-Gain 61,06; kategori sedang) dibandingkan kelas yang belajar melalui pembelajaran konvensional (N-Gain 30,36; kategori rendah), dan perbedaan tersebut terbukti signifikan secara statistik. Temuan ini memperluas bukti empiris bahwa efektivitas pembelajaran IPAS tidak hanya dipengaruhi oleh pemilihan model pembelajaran ataupun media digital secara terpisah, tetapi oleh keterpaduan keduanya dalam membangun pengalaman belajar yang mendukung pemahaman konsep peserta didik. Hasil penelitian ini sekaligus memberikan landasan bagi pengembangan pembelajaran IPAS yang lebih adaptif dan kontekstual pada jenjang sekolah dasar.